Unveiling the Impact of Mobile Game Addiction and Negative e-WOM on Purchase Intention in Online Gaming Applications - Putra, Ronaldo Yolanda; Nuzula, Ifta Firdausa; Hidayat, Agus Syarip (The Indonesian Institute of Science and Technology Research, 2024)
This study investigated the impact of mobile game addiction, loyalty, and negative e-WOM on purchase intention in online gaming applications, using a questionnaire distributed to PUBG Mobile players through game communities on WhatsApp and Telegram. The study found that online game addiction has a significant effect on online game loyalty, and online game loyalty has a significant effect on purchase intention. Additionally, online game addiction has a significant effect on negative e-WOM, and negative e-WOM has a significant effect on purchase intention. Game addiction also has a significant effect on purchase intention. These findings contribute to filling the research gap in the literature on the relationship between game addiction, loyalty, negative e-WOM, and purchase intention. The study emphasizes the importance of game developers and marketers understanding and managing these factors to encourage purchase intention in online gaming applications.